Could We Achieve the On‐Line Measurements of the Optical Fractal Dimensions of Black Carbon? - Gang Zhao; Min Hu; Weili Lin; Ye Kuang; Jie Sun; Linghan Zeng; Chunsheng Zhao (Geophysical Research Letters)
Abstract Significant uncertainties exist in quantifying black carbon (BC) warming effects on earth due to the variation in its light absorption abilities, which depend on its morphology. The fractal dimension (Df) of BC aggregates, is a critical morphology factor determining BC's absorption properties. However, Df cannot be measured online, making it hard to study the BC morphology evolution during atmospheric aging processing. We propose a novel method to measure BC's Df by establishing the relationship between BC's mobility diameter (Dm), Df, and mass concentration (m0). This method enables to measure the Df of BC aggregates online by measuring their Dm and m0 concurrently with an accuracy of 0.15. Field measurements show that the ambient BC Df ranges between 2.14 and 2.41 at a suburban site in China. This approach provides an efficient means to measure Df online, making it possible to track the ambient BC morphology evolution and constrain the BC optical and radiative properties.